Care of puerperal women with postpartum hemorrhage: prevention and management (Research, Society and Development, 2022)
Postpartum hemorrhage (PPH) is defined as a loss of 500 ml of blood or more within 24 hours after delivery, most of these deaths can be avoided with the use of prophylactic uterotonics being the main source of prevention in the third phase of delivery. delivery and timely through proper management. The objective of this work is to analyze assistance in the prevention and management of postpartum hemorrhage, to ensure the prevention, stabilization and monitoring of the patient in order to solve any future problems, also contributing to the reduction of risk and maternal deaths. This is an integrative review study, where a search was carried out in the following databases: Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and Spanish Bibliographic Index in Sciences of Health (IBECS). The following descriptors were used to search for articles: “Postpartum Hemorrhage”, “Postpartum Period” and “Pregnant Women”. The inclusion criteria defined for the selection of articles were: articles available online, in full, in Portuguese, English and Spanish, and indexed in the aforementioned databases in the years 2012 to 2022. As exclusion criteria: articles that did not include the theme and repeated studies in the databases. In view of the above, we can see the care provided to the puerperal woman, such as the evaluation of loquiation and vital signs, which can facilitate the perception of the beginning of the hemorrhage, facilitating the immediate management and reducing the progression of the case.